New Therapeutic Scenarios in the Context of Adjuvant Treatment for HR+/HER2−Breast Cancer: The Possible Role of Ribociclib in Treatment Algorithms for Stage II and III - Nicola Battelli; Carmela Mocerino; Michele Montedoro; Mirco Pistelli; Ilaria Portarena; Mario Rosanova; Tina Sidoni; Patrizia Vici (Current Oncology)
Early breast cancer (EBC) treatment has evolved from radical surgery to a multidisciplinary approach, integrating radiotherapy, chemotherapy, targeted therapy, and hormone therapy with surgery to ensure the best possible outcome. Despite these advancements, hormone receptor-positive (HR+)/Human Epidermal Growth Factor Receptor 2-Negative (HER2−) EBC still faces high recurrence rates after endocrine therapy. A panel of oncologists from Central-Southern Italy discussed the profile of ribociclib as an adjuvant therapy, based on the results of the NATALEE study, focusing on efficacy, safety, patient profiles, and regional challenges in treatment access. The experts identified ribociclib as suitable adjuvant treatment for stage II and III HR+/HER2− EBC patients, including those without lymph node involvement but with biologically aggressive disease. In their view, ribociclib could be an interesting option for patients not eligible for chemotherapy due to contraindications. Key challenges in translating the evidence on ribociclib in EBC into clinical practice include treatment duration, patient follow-up, and adverse events management. Strategies to address these challenges range from telemedicine and support from local clinics to tailored communication to improve adherence. Ribociclib is expected to significantly impact adjuvant treatment for HR+/HER2− EBC by addressing broader patient needs and potentially improving long-term outcomes through enhanced adherence and personalized management strategies.